2019
DOI: 10.1016/j.cell.2019.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidase-1 Is an Adhesion Receptor for Neutrophil Recruitment in Lungs and Liver

Abstract: Highlights d Dipeptidase 1 (DPEP1) serves as a vascular adhesion molecule in lungs and liver d DPEP1 acts as a physical adhesion receptor independent of its dipeptidase activity d Targeting DPEP1 reduces mortality in murine models of sepsis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 90 publications
2
83
0
Order By: Relevance
“…5 Dipeptidase-1, a major adhesion receptor on hepatic endothelial cells, also mediates neutrophil adhesion in an enzyme activityindependent manner. 6 Apoptotic neutrophils are eliminated mainly by macrophages, which contributes to localized tissue inflammation. Meanwhile, activated macrophages secrete both G-CSF and granulocyte-macrophage colony-stimulating factor (GM-CSF) to slow neutrophil apoptosis.…”
Section: The Inherent Role Of Neutrophilsmentioning
confidence: 99%
“…5 Dipeptidase-1, a major adhesion receptor on hepatic endothelial cells, also mediates neutrophil adhesion in an enzyme activityindependent manner. 6 Apoptotic neutrophils are eliminated mainly by macrophages, which contributes to localized tissue inflammation. Meanwhile, activated macrophages secrete both G-CSF and granulocyte-macrophage colony-stimulating factor (GM-CSF) to slow neutrophil apoptosis.…”
Section: The Inherent Role Of Neutrophilsmentioning
confidence: 99%
“…This work indicates that the lung is an important host defense niche for the detection and capture of systemic pathogens, and requires cooperation between the vascular endothelium and marginated neutrophils (Yipp et al, 2017). In the search for new adhesion molecules that support neutrophil retention in the lung during inflammation, an in vivo functional screen surprisingly identified dipeptidase-1 (DEPEP1) (Rajotte and Ruoslahti, 1999;Choudhury et al, 2019). DEPEP1, a membrane enzyme expressed by activated pulmonary endothelium, was shown to support neutrophil adhesion, independent of its enzymatic activity.…”
Section: Neutrophils Marginate Within the Microcapillaries Of The Lungmentioning
confidence: 99%
“…DEPEP1, a membrane enzyme expressed by activated pulmonary endothelium, was shown to support neutrophil adhesion, independent of its enzymatic activity. Moreover, genetic deletion studies and use of a blocking peptide showed that neutrophil adhesion and recruitment in the inflamed lung was significantly attenuated in the absence of DEPEP1 during sepsis (Choudhury et al, 2019). Finally, when the DEPEP1 blocking peptide was used therapeutically in mice administered with a lethal dose of LPS, it showed a remarkable survival effect and an impressive reduction in neutrophil recruitment into the inflamed lung (Choudhury et al, 2019).…”
Section: Neutrophils Marginate Within the Microcapillaries Of The Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the research of dipeptidase mainly focuses on animal (O'Dwyer et al, 2009;Andreyeva et al, 2019;Choudhury et al, 2019), human pathogenic bacteria (Chang et al, 2010;Toyotome et al, 2015) or plant pathogenic bacteria (Kumar et al, 2014). Function reports of dipeptidases are mostly limited to virulence and growth in microorganisms, while there is little information regarding the effect of dipeptidases on stress tolerance in microorganisms.…”
Section: Discussionmentioning
confidence: 99%